Animal breeding in developing country situations in Africa - Trail, J.C.M. (Nebraska University, 1986)
Studies the broad groups of cattle in Africa in relation to the main ecological zones. Indicates the possibilities for bringing about changes through application of animal breeding techniques. Reviews past cattle breeding research in Africa. Summarises ILCA's work with national research organisations to assemble available information on breeds and breeding. Gives examples of animal breeding work in Africa.